Expected and possible unexpected consequences of ending the eviction moratorium - Jack Tsai (Elsevier, 2021)
The U.S. Supreme Court ended the federal moratorium on evictions that was in effect from May 2020-August 2021 during the Coronavirus Disease 2019 (COVID-19) pandemic. The end of an unprecedented national eviction moratorium has public health implications for housing, health, and homelessness. Accumulation of eviction filings, unpaid rent, tenant moral hazards, deteriorated tenant-landlord relationships, and increased transmission of COVID-19 and rates of homelessness are possible consequences that need to be prepared for as the federal eviction moratorium has ended. Innovative approaches and solutions can be taken that build upon existing knowledge and infrastructure for rental assistance, legal aid, and homeless prevention.